Peningkatan Kesehatan dan Kesejahteraan Masyarakat Melalui Pendampingan Perencanaan Apresiatif Desa Di Desa Benelan Kidul Kecamatan Singojuruh Kabupaten Banyuwangi - Muhamad Annas; Sumari Mawardi; Munawir Munawir (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
This dedication was carried out to improve the health and welfare of the community through the assistance of Village Appreciative Planning in Benelan Kidul Village, Singojuruh Subdistrict, Banyuwangi Regency. The results of community service show that the community realizes that the problem of waste must be handled together with all elements of the community. Clean and healthy living is the desire of all citizens. Household Waste Sorting is based on the results of the Healthy Lifestyle Training that has been carried out in each hamlet with PKK cadre participants and study group mothers. The transportation system from households is temporarily collected in a sorting place located in each hamlet, where the selection points are determined by the hamlet head. Waste sorting is carried out in temporary sorting sites located in each hamlet by sorting out Organic and Inorganic waste. Where for organic waste is managed into fertilizer while inorganic waste, especially plastic waste will be managed into plastic ore. Garbage Bank is a business unit that is under the coordination of BUMDes so that marketing of organic and inorganic waste sorting results will be coordinated through BUMDes.